Studies on Effect of Concentrated Sulphuric Acid Treatment on Germination of Rubus ellipticus Seed - Bhagat, S.; Singh, Virendra (Indian Forester, 1995)
The study was conducted to evaluate the effect of concentrated sulphuric acid treatment on germination of Rubus ellipticus seed and it was observed that fresh seed treated with acid for 20-30 minutes exhibited maximum germination whereas stored seed (3 months) required acid treatment for 45-60 minutes duration for maximum germination.